SISTEM INFORMASI PELACAKAN KERUSAKAN LAPTOP DENGAN DUKUNGAN MODUL SISTEM PAKAR - Made Ngurah Satya Wibawa Putra; Duman Care Khrisne; I Ketut Wijaya (Jurnal SPEKTRUM, 2021)
Thexhighxusexofxlaptops today by individuals will affect the condition of laptop andcausing various damage to the laptop itself. The limited knowledge by user solving the problemson a laptop make user have to consult an expert technician to obtain a solution for existingdamage. On the other hand, many and varied defects of laptops, as well as the hectic tasks thatmust be performed by technicians, causing problems on the side oftechnicians.xUtilizationxofxinformation technologyxcanxbexaxsolutionxtoxovercomexproblemsbetween users and technicians. By building a web-based expert system to get the result ofdamage diagnosis and repair solutions, hopefully it can help users find out what problems ontheir laptop and make it easier for technician to deal with damage. This research using webbasedforward chaining as system method. This system can display the results of a laptopdamage diagnosis that it come from symptoms asked by system and repair solution fromdamage diagnosis. Basedxonxthextestxresultsxusingxblack boxxmethod,xthexsystems hasfunction that according with system design, can run according to orders, andhavexbeenxdeclaredxsuccessful.xBasedxonxthexresultxofxthexSystemxUsabilityScalex(SUS)xtest, this system obtainxscorex82.5, which means that the whole system can beaccepted as functioning well on the web.